(untitled) (ACME, 2020)
Since 2008 the Centro Apice (Università degli Studi, Milan) has kept the study materials and papers which once belonged to the nobleman and scholar Girolamo Luigi Calvi (1791-1872), who owes his fame to the publication, between 1859 and 1869, of the three volumes of the Notizie sulla vita e sulle opere dei principali architetti scultori e pittori che fiorirono in Milano durante il governo dei Visconti e degli Sforza, which is the very first history of Lombard artists. This article, based on my PhD research, points out the most important news written in the unpublished fourth volume of the Notizie, made up by the biographies of Bernardino Luini, Giampietrino, Giovanni Antonio Boltraffio, Cesare da Sesto and Salaino, which Calvi would like to print as natural sequel to the third book, devoted to Leonardo da Vinci. Besides that, it draws attention to Calvi’s methodology, still tied to 18th-century erudition, but also open to the modern archival research and live examination of the artworks.